2015
DOI: 10.1128/aem.03523-14
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis of Xylan Utilization Systems in Paenibacillus sp. Strain JDR-2

Abstract: b Xylans, including methylglucuronoxylans (MeGX n ) and methylglucuronoarabinoxylans (MeGAX n ), are the predominant polysaccharides in hemicellulose fractions of dicots and monocots available for conversion to biofuels and chemicals. Paenibacillus sp. strain JDR-2 (Pjdr2) efficiently depolymerizes MeGX n and MeGAX n and assimilates the generated oligosaccharides, resulting in efficient saccharification and subsequent metabolism of these polysaccharides. A xylan utilization regulon encoding a cellassociated GH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 48 publications
2
30
0
Order By: Relevance
“…The cause for the high abundance of α-amylase was unclear. A recent transcriptomic study suggested that genes encoding amylases in Paenibacillus could be induced by xylan [51]. This was, however, unlikely in our case, because the protein abundance of the α-amylase decreased significantly over the cultivation period, as detailed below.…”
Section: Resultsmentioning
confidence: 64%
“…The cause for the high abundance of α-amylase was unclear. A recent transcriptomic study suggested that genes encoding amylases in Paenibacillus could be induced by xylan [51]. This was, however, unlikely in our case, because the protein abundance of the α-amylase decreased significantly over the cultivation period, as detailed below.…”
Section: Resultsmentioning
confidence: 64%
“…The production of multiple xylanases in microorganisms has evolved diverse enzymes with different physiological properties for more effective degradation of the complex plant biomass 20 21 . The presence of multiple xylanase isoforms in P. oxalicum GZ-2 was observed after 7 days of fermentation in previous studies using zymography 5 18 .…”
Section: Discussionmentioning
confidence: 99%
“…JDR-2 (Pjdr2) originally isolated from sweetgum wood ( Liquidambar styraciflua ) disks exposed to surface soils has been shown to completely utilize the lignocellulosic polymer glucuronoxylan (GX n ). Previous studies showed that growth on minimal media supplemented with polymeric xylan was preferred to that on simple sugars such as xylose, glucose, or arabinose [ 1 , 2 ]. These studies indicated that efficient xylan utilization is attributable, in part, to a 157 kDa GH10 β-1,4-endoxylanase (Xyn10A 1 ) containing carbohydrate binding modules (CBM) for binding to polysaccharides and surface layer homology (SLH) domains for cell-association.…”
Section: Introductionmentioning
confidence: 99%
“…Genomic organization of xylan utilization genes ( a ) assigned a role in xylan utilization in Pjdr2. For a complete list see Additional file 1 [ 1 ]. Genetic organization of barley β-glucan ( b ) and starch ( c ) utilization regulons consisting of genes encoding extracellular multi-modular cell-associated or secreted glycoside hydrolases for depolymerization, ABC transporters for assimilation of the generated oligosaccharides, and intracellular glycoside hydrolases for further processing and metabolism.…”
Section: Introductionmentioning
confidence: 99%